Qur'an Matriculation Strategy in Pesantren Education: Strengthening the Competence of New Students Towards Achieving Internal Curriculum - Suherman Suherman (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
The Qur'an matriculation program in Islamic boarding schools has an important role in preparing new students to follow the internal curriculum well. This study aims to analyze the strategy and effectiveness of the Qur'an matriculation program at the Minhaj Shahabah Islamic Boarding School Bogor in standardizing the ability to read the Qur'an of new students and preparing them to follow subjects in the internal curriculum of the pesantren, such as tahfidzul Qur'an, Arabic, aqidah, fiqh, nahwu shorof, and other diniyyah subjects. The research method used is a qualitative approach with data collection techniques through observation, interviews, and document analysis related to the Qur'an matriculation program. The results showed that the Qur'an matriculation program succeeded in creating a consistent standard of Qur'an reading ability among new learners. Through an intensive approach in learning Qur'an recitations, new learners can smoothly follow the internal curriculum of pesantren. This research provides a deeper understanding of the importance of the Qur'an matriculation program in pesantren education and its positive impact on the preparation of new learners in following internal curriculum subjects. The implications of this research can be a foundation for similar educational institutions to develop effective matriculation programs in supporting the achievement of internal curriculum and the development of learners' competencies.